The Existence of the Implementation of Academic Supervision of Principals in Improving the Personality Competencies of Early Childhood Teachers: A Case Study in the Context of Deep Learning - Sari, Elistiana Wulan; Robi’ah, Eneng; Soro, Suharyanto; Mardiana, Dinny (Civiliza Publishing, Indonesia., 2025)
The improvement of the quality of early childhood education is not only determined by the pedagogical and professional abilities of teachers, but also by personality competencies that play an important role in creating a safe, comfortable, and meaningful learning environment for children. Early childhood education teachers are required to have emotional stability, patience, integrity, exemplary attitude, and the ability to build positive relationships with students. However, conditions in the field show that the implementation of academic supervision in many PAUD units is still administrative. Supervision is more focused on the implementation of school programs and learning assessments, while the personal needs and personality development of teachers are often not the main concerns. This study aims to describe and analyze the implementation of academic supervision by school principals in improving the personality competence of PAUD teachers through a deep learning approach. This research uses a qualitative descriptive method with a constructivist paradigm and was conducted as a case study at Ceria Children's Family Planning, Bandung. Data were collected through classroom observations, in-depth interviews, and documentation studies. Data analysis was carried out using the Miles and Huberman interactive model which included data reduction, data presentation, and conclusion drawn. The results of the study show that (1) Academic supervision that is carried out in a planned, humanistic, and sustainable manner can strengthen teachers' personality competencies; (2) The application of deep learning principles in supervision encourages teachers to reflect on themselves, manage emotions, increase a sense of responsibility, and develop a professional attitude in learning. This approach is in line with humanistic theory that emphasizes the development of individual potential through support, empathy, and positive appreciation for teachers. The conclusion of the study is that the implementation of academic supervision of school principals can improve the personality competence of PAUD teachers in the context of deep learning. Therefore, academic supervision needs to be carried out consistently with a more humanist approach in order to support the development of the personality of PAUD teachers in a sustainable manner.